Influence of growth regulators on the activity of amylolytic enzymes in spring wheat grain - I.I. Seregina; M. Anka; N.N. Novikov; S.L. Belopukhov; I.I. Dmitrevskaya (Известия высших учебных заведений. Поволжский регион: Естественные науки, 2022)
Background. It is known that one of the main indicators of biochemical changes occurring during seed germination is an increase in the enzymatic activity of the amylolytic complex. In this regard, the purpose of the studies was to study the enzymatic activity of various isoforms of the amylase complex of grains of spring soft wheat variety Darya at rest and during germination, depending on the use of growth regulators. As a result of the research, the following issues were studied: the effect of plant growth bioregulators on the activity of α-amylase and β-amylase isoforms in dormant and germinated grain. Materials and methods. Under the conditions of field experiments, spring wheat (Ttriticum aestivum L.) of the Darya variety was grown using foliar treatment of plants with various growth regulators during the growing season. After harvesting, the activity of acidic, neutral and alkaline isoforms of the amylolytic complex in dormant and germinated grain was determined in the resulting wheat grain to assess the quality of the seed material. Results. It was found that the activity of isoforms of amylase enzymes depended on the growth regulators used during the growing season. It was found that in the dormant grain, the biological preparation Hardy and, as well as a mixture of Hardy and Ferovit preparations, showed the highest efficiency on the activity of α-amylase isoforms, which determines the good seed quality of spring wheat grain. The use of a protective-stimulating complex biological product and growth regulator Ferovit in the cultivation of spring wheat had a significant effect on the activity of α-amylase isoforms during the germination of the resulting grain, which determines the high level of endosperm solubility and improves the growth functions of seedlings. It was revealed that the changes occurring in the enzymatic activity of the amylolytic complex of wheat grain were determined by the different effectiveness of the active substance of the drugs used.